Transmigrasi di Indonesia: Tinjauan Sistematis tentang Arah Kebijakan, Dampak Sosial-Ekosistem, dan Implikasi bagi Administrasi Desa (1959-2025) - Riamona Sadelman Tulis; Agus Pramusinto; Agustinus Subarsono; Bevaola Kusumasari (Administratio, 2025)
Transmigration has long served as a tool for regional equity and reducing population pressure in Java-Bali, but its success was often judged by physical outputs alone. This study synthesizes cross-era evidence to (i) map shifting policy rationales and instruments, (ii) summarize recurring socio-ecological impacts, and (iii) draw operational lessons for village governance. Using a Scopus-based Systematic Literature Review of publications from 1959 to 2025, 95 articles were selected after title, abstract, and full-text screening. Thematic synthesis covers three periods: 1959-1999, 2000-2014, and 2015-2025. Over time, there has been a shift from standardized interventions to context-sensitive and governance driven approaches: spatial planning based on land and water suitability, basic services aligned with livelihood cycles and market access, community forest management, and stronger procedural justice through inclusive participation and rights recognition. Recent trends emphasize rapid land conversion, frontier related relocations, and the need for conflict mediation at the village level. Today, transmigration success is better measured by the quality of spatial choices, livelihood stability, and policy legitimacy. Village administrations play a central role through participatory socio-biophysical mapping, adaptive service SOPs, socio-ecological regulations, and transparent mediation tools bridging national policies with practical, local outcomes.